(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The proximate and minerals composition of the fruits pulp and seeds of parkia biglobosa (African locust bean) were evaluated and the results were compared with World Health Organization (WHO).The fruit pulp parkia biglobosa contained 33.2%, 10.6%, 2.50%, 6.30% and 47.4% moisture, Ash value, fat (ether extract), protein and carbohydrate respectively while the seeds of parkia biglobosa also contained 20.2%, 17.4%, 20%, 6.65% and 35.75% for moisture content, ash content, fat (ether extract), protein and carbohydrate respectively. The fruits and seeds of parkia biglobosa are rich in Na, K, Ca, Mg and Fe which were differed to some extents. The fruits contain 2.7 mg/100 g, 209 mg/100 g, 35.5 mg/100 g, and 27 mg/100 g, 0.556 mg/100 g Na, K, Ca, Mg and Fe respectively while the seeds contained 0.133 mg/100 g, 1.05 mg/100 g, 0.1 mg/100 g, 11.16 mg/100 g and 0.148 mg/100 g for Na, K, Mg, Ca and Fe respectively. Both the fruits and seeds are very good sources of mineral elements because the mineral composition results showed that there are very much similarities with the daily requirements of the tested elements by WHO 2011, even though the values are little bit higher than the standard. The fruits and seeds of the samples contain certain amount of energy given food and health preserving ones.